1996
DOI: 10.1111/j.1524-4725.1996.tb00640.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine mRNA Changes during the Treatment of Hypertrophic Scars with Silicone and Nonsilicone Gel Dressings

Abstract: This study demonstrates that silicone is not a necessary component of occlusive dressings in the treatment of hypertrophic scars. The pathogenesis of hypertrophic scars is further elucidated by demonstrating that there is molecular evidence for extensive connective tissue remodeling occurring during occlusive dressing therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
33
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 10 publications
2
33
1
Order By: Relevance
“…The decrease in both IL-6 and CXCL8 secretion was characteristic for the HTscar model only and, therefore, it would now be interesting to determine whether Htscars in vivo also showed decreased expression of these cytokines. In literature, no consensus was reached whether IL-6 and CXCL8 are up-or down-regulated during HTscar formation (Zhou et al, 1997;Ricketts et al, 1996;Wang et al, 2011). The confusion may be due to size, location, and age of the studied scar samples.…”
Section: Discussionmentioning
confidence: 99%
“…The decrease in both IL-6 and CXCL8 secretion was characteristic for the HTscar model only and, therefore, it would now be interesting to determine whether Htscars in vivo also showed decreased expression of these cytokines. In literature, no consensus was reached whether IL-6 and CXCL8 are up-or down-regulated during HTscar formation (Zhou et al, 1997;Ricketts et al, 1996;Wang et al, 2011). The confusion may be due to size, location, and age of the studied scar samples.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, several uncontrolled SGS and FLPDL hypertrophic scar studies have included hypertrophic scars younger than 1 year. 12,14,15,22,25,26 In these articles, it is not clear whether the hypertrophic scars would have resolved without treatment. A control site was included in our study to account for the possibility of spontaneous hypertrophic scar resolution.…”
mentioning
confidence: 99%
“…25 However, in 1989, Ahn et al 22 found no histological evidence of silicone in biopsy specimens of SGS-treated scars. Results of more recent studies 13,14,39 show that occlusive dressings, with or without silicone, can be effective in treating hypertrophic scars and conclude that hydration, not silicone, is what modulates scar formation. A reduction in fibroblast production and collagen proliferation in hydrated or occluded wounds has also been reported.…”
mentioning
confidence: 99%
See 2 more Smart Citations